2008
DOI: 10.1167/8.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Highlight disparity contributes to the authenticity and strength of perceived glossiness

Abstract: The disparity of highlights on specular reflecting surfaces usually differs from the disparity of the surface points. A. Kirschmann (1895) proposed that this fact may be used as a binocular cue for gloss perception. This was confirmed by A. Blake and H. Bülthoff (1990) who found that subjects judged the glossiness of convex ellipsoidal surfaces as most realistic if the disparity of the highlights was close to the physical correct one. Extending on this finding, we investigate more closely whether the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 20 publications
1
47
1
Order By: Relevance
“…Doing so, we avoid conflicts, however highlights seem to be painted onto the surface. This is a significant shortcoming, as it is known, that highlight disparity is a strong factor for the perception of gloss [Blake and Bülthoff 1990;Hurlbert et al 1991;Sakano and Ando 2010] and material authenticity [Wendt et al 2008]. Nevertheless on-surface highlights are quite common, presumably for three main reasons: Because artists consider them to be more pleasant to watch; because of performance (e. g., in games that can not afford to shade twice [Sousa et al 2012]); and because the necessary information is missing (e. g., in 2D-to-3D conversion).…”
Section: Introductionmentioning
confidence: 99%
“…Doing so, we avoid conflicts, however highlights seem to be painted onto the surface. This is a significant shortcoming, as it is known, that highlight disparity is a strong factor for the perception of gloss [Blake and Bülthoff 1990;Hurlbert et al 1991;Sakano and Ando 2010] and material authenticity [Wendt et al 2008]. Nevertheless on-surface highlights are quite common, presumably for three main reasons: Because artists consider them to be more pleasant to watch; because of performance (e. g., in games that can not afford to shade twice [Sousa et al 2012]); and because the necessary information is missing (e. g., in 2D-to-3D conversion).…”
Section: Introductionmentioning
confidence: 99%
“…Viewing surfaces 931 of reduced bumpiness, but at closer viewing distances, might mean 932 that observers are better able to perceive a finer scale of texture,known about this potential factor, but it is undeniably an imporEven before any detailed study of the perception of gloss began, 938 binocular disparity had already been identified as a potentially 939 invaluable source of information. Kirschmann (1895, as cited inWendt, Faul, & Mausfeld, 2008) proposed that the disparity of 941 highlights on specularly reflecting surfaces usually differs from 942 the disparity produced by points on the surface itself. Czepluch 943(1984( , as cited in Sève, 1993 also emphasised the importance of 944 binocular disparity.…”
mentioning
confidence: 99%
“…Therefore, it is necessary to depict gloss more carefully in stereoscopic rendering when scenes with highly glossy objects are considered. Wendt et al [16] indicated that highlight disparity can improve material authenticity and the strength of gloss by using several visual stimuli tests with the Phong lighting model. In computer graphics, Vangorp et al [17] performed a psychophysical experiment related to material discrimination by rendering synthetic images with a global illumination technique under natural environment lighting.…”
Section: Human Perception Of Glossmentioning
confidence: 99%